EFFECT OF ISLAMIC WORK ETHICS ON JOB PERFORMANCE: MEDIATING ROLE OF INTRINSIC MOTIVATION - Ud Din, Maaz; Khan, Faisal; Khan, Usman; Kadarningsih, Ana; Astuti, Sih Darmi (IJIBE (International Journal of Islamic Business Ethics), 2019)
The determination of this research is to examine the effect of Islamic work ethics on job performance and intrinsic motivation. This study also try to investigate the mediating role of intrinsic motivation on the association between Islamic Work Ethics and job performance. Nonprobability sampling, method was used. Data were collected through adopted questionnaires from 310 teachers of different Universities situated in Malakand Division, KP-Pakistan. SPSS and AMOS were used for Statistical tests. Empirical results indicate that there is a significant positive association between Islamic work ethics, Job performance and intrinsic motivation. The study determined that the idea of Islamic work ethics works as a therapy for the emergent ethical crisis of education sector of Pakistan which should be pervaded in organizational culture for sustainable job performance and growth. Further, study explain that intrinsic motivation mediates the association between Islamic Work Ethics and Job Performance. Implications and upcomingstudy recommendations are discuss in the conclusion.